Diferentes espessantes, níveis de gordura e lactossoro em creme de ricota - Gusso, Ana Paula (2013)
The consumption of low-calorie foods has increased in recent decades. The industries that are committed to health promotion have been developing technologies for food production with reduced fat, meeting the demands of consumers. Thus, this study began with a review of the behavior of different thickeners (guar gum, carrageenan, xanthan and tara) in experimental ricotta cream, and compared these with commercial ricotta cream. The various thickeners used in this study had a significant influence on instrumental and sensory firmness, being guar gum, the selected thickener for the next phase. The second phase of this work was conducted through the factorial planning 22 having whey and milk cream as independent variables. The factorial planning performed was the type Central Composite Rotational Delineation (CCRD), totaling 12 trials, being four factorial, four axial, one central point with three repetitions and one control treatment. The treatments were subjected to physico-chemical, microbiological and sensory analysis, as well as their stability assessed during shelflife. The use of whey as a partial fat substitute reduced by 50% the contents of this variable for the T8 treatment when compared to the control treatment. This reduction had no significant influence on the concentration of fatty acids present in creams. Generally, the pH of ricotta creams were slightly higher in the end of the storage period in relation to their averages in the beginning of the shellife. Lipid oxidation was enhanced in the presence of whey, a synergistic element for this analysis. Whey increased the instumental firmness of the creams when compared to the control treatment. The response surfaces generated in sensory acceptance analysis showed the existence of an optimal region for the best sensory grades in relation to attributes observed, in the range of 5-15% fat and 9-21% of whey. The cream selected as preferred by judges at the end of the sensory analyses of preference showed 5% fat and 10% whey in its composition.